Examining Sanction Type and Drug Offender Recidivism: A Register-Based Study in Finland - Miller, Bryan Lee (American journal of criminal justice, 2022)
Nordic countries incarcerate offenders at much lower rates in comparison with incarceration rates in the United States, and reincarcerate fewer people per capita. Non-custodial alternatives to sanctions, including fines and community service, are used extensively in Finland to reduce negative effects of institutionalization and subsequent disadvantage caused by incarceration. The nature of drug-involved offenders within the Finnish system is reviewed in light of current research about the effectiveness of incarceration and deterrence-based approaches for drug offenders. Employing a 2014 sample from register data (consisting of official government records) of drug offenders in Finland with a 3-year recidivism period, this study utilizes a genetic matching procedure to compare offenders who received fines, conditional sentences (probation), or incarceration. While recognizing that numerous confounding variables affect incarceration, we compare a matched sample of drug offenders and the sanctions they have received from the Finland judicial system to determine whether offenders who initially receive a fine or a conditional sentence reenter the correctional system at different rates than those who are incarcerated. After matching, results found no significant differences between offenders receiving incarceration sentences or those who received noncustodial sentences (fine, or conditional sentence) for general and drug-related recidivism. These results are presented within the context of the Finnish corrections system in order to inform the criminal justice community about culture, incarceration, and process differences that could positively affect working with drug offenders in other localities.